Cost-benefit analysis of the community patent - Jérôme Danguy; Bruno Van Pottelsberghe de la Potterie (Bruegel, 2009)
For more than 40 years, governments and professional associations have acted, voted or lobbied against the implementation of the Community Patent (COMPAT). The econometric results and simulations presented in this paper suggest that, thanks to its attractiveness in terms of market size and a sound renewal fee structure, the COMPAT would drastically reduce the relative patenting costs for applicants while generating more income for the European Patent Office and most national patent offices. The loss of economic rents ( exteuro400 million would be lost by patent attorneys, translators and lawyers) and the drop of controlling power by national patent offices elucidate further the observed resistance to the Community Patent.
Keywords: O34; O38; P14; 330; patent systems; community patent; patenting cost; renewal fees; maintenance rate; Patentrecht; EU-Recht; Kosten-Nutzen-Analyse; EU-Staaten